The peopling of Europe and the cautionary tale of Y chromosome lineage R-M269 - Busby, G; Brisighelli, F; Sánchez-Diz, P; Ramos-Luis, E; Martinez-Cadenas, C; Thomas, MG; Bradley, D; Gusmão, L; Winney, B; Bodmer, W; Vennemann, M; Coia, V; et al. (2012)
Recently, the debate on the origins of the major European Y chromosome haplogroup R1b1b2-M269 has reignited, and opinion has moved away from Palaeolithic origins to the notion of a younger Neolithic spread of these chromosomes from the Near East. Here, we address this debate by investigating frequency patterns and diversity in the largest collection of R1b1b2-M269 chromosomes yet assembled. Our analysis reveals no geographical trends in diversity, in contradiction to expectation under the Neolithic hypothesis, and suggests an alternative explanation for the apparent cline in diversity recently described. We further investigate the young, STR-based time to the most recent common ancestor estimates proposed so far for R-M269-related lineages and find evidence for an appreciable effect ofmicrosatellite choice on age estimates. As a consequence, the existing data and tools are insufficient to make credible estimates for the age of this haplogroup, and conclusions about the timing of its origin and dispersal should be viewed with a large degree of caution. © 2011 The Royal Society.